Analysis of the figure of the teacher in postmodernism times - Trujillo Vargas, José Jesús; Perlado Lamo de Espinosa, Ignacio; Barroso Tristán, Jose María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we carry out an investigative-theoretical-reflexive approach on the effects of postmodernism and postmodernity in today’s society and in the educational field in particular (focusing on the role of the teacher). Under the guise of the common good: greater equality, environmentalism, attention to diversity, respect for differences..., one of the visions of postmodernism makes it the scapegoat of capitalism, causing it to continue to be engulfed, implicitly generating a vision unequivocal and little conducive to criticism by the bulk of society, which accepts it as part of that common good. Given this, what can we do from our educational role? maximum.